Frequent nut consumption and risk of coronary heart disease in women: prospective cohort study - Hu, Frank B (British Medical Journal, 1998)
OBJECTIVE: To examine the relation between nut consumption and risk of coronary heart disease in a cohort of women from the Nurses’ Health Study. DESIGN: Prospective cohort study. SETTING: Nurses’ Health Study. SUBJECTS: 86 016 women from 34 to 59 years of age without previously diagnosed coronary heart disease, stroke, or cancer at baseline in 1980. MAIN OUTCOME MEASURES: Major coronary heart disease including non-fatal myocardial infarction and fatal coronary heart disease. RESULTS: 1255 major coronary disease events (861 cases of non-fatal myocardial infarction and 394 cases of fatal coronary heart disease) occurred during 14 years of follow up. After adjusting for age, smoking, and other known risk factors for coronary heart disease, women who ate more than five units of nuts (one unit equivalent to 1 oz of nuts) a week (frequent consumption) had a significantly lower risk of total coronary heart disease (relative risk 0.65, 95% confidence interval 0.47 to 0.89, P for trend=0.0009) than women who never ate nuts or who ate less than one unit a month (rare consumption). The magnitude of risk reduction was similar for both fatal coronary heart disease (0.61, 0.35 to 1.05, P for trend=0.007) and non-fatal myocardial infarction (0.68, 0.47 to 1.00, P for trend=0.04). Further adjustment for intakes of dietary fats, fibre, vegetables, and fruits did not alter these results. The inverse association persisted in subgroups stratified by levels of smoking, use of alcohol, use of multivitamin and vitamin E supplements, body mass index, exercise, and intake of vegetables or fruits. CONCLUSIONS: Frequent nut consumption was associated with a reduced risk of both fatal coronary heart disease and non-fatal myocardial infarction. These data, and those from other epidemiological and clinical studies, support a role for nuts in reducing the risk of coronary heart disease.